Size-independent unipolar charging of nanoparticles at high concentrations using vapor condensation and its application for improving DMA size-selection efficiency. (July 2018) - Ock, Yoohyun; Kim, Jeonggeon; Choi, Indae; Kim, Dae Seong; Choi, Mansoo; Lee, Donggeun
Abstract: The goal of this study was to achieve a significant improvement in the size-selection performance of DMA, by combining unipolar charging and the condensational method of growing nanoparticles. We developed a size-independent unipolar charger consisting of a saturator, a condenser, a corona charger, and an evaporator. Starting with a two-fluid mixing design, a porous-alumina-lined saturator was tested in terms of the size uniformity of particles after their condensational growth in a subsequent condenser. 20-nm Ag and 65-nm NaCl polydisperse nanoparticles were successfully grown into droplets of few micrometers with a geometric standard deviation of 1.20 or less. A simple model was also developed to explain the heat and mass transfer occurring in the saturator and condenser, resulting in predictions of particle growth that agreed with experimental results. The entire charging system was experimentally evaluated in terms of size dependencies of charging efficiency and charge numbers. The results revealed that 52% of the nanoparticles were uniformly charged and released with a charge number of + 32, irrespective of the particle sizes. A regular nano DMA, using the proposed size-independent charging system in place of a bipolar charger, was finally tested to determine its productivity when size-classifying particles. It was found that the proposed charger, when combined with the DMA, was eight times more efficient compared to the bipolar charger, and became more advantageous as the target particle size decreased. These promising results were reconfirmed by TEM image analysis of the produced monodisperse particles. Highlights: We proposed a new concept of size-independent unipolar charging of nanoparticles. Our unique approach is to combine vapor condensation with corona discharge. Through a series of preliminary tests, the proposed concept was experimentally proven. The proposed charger was eight times more efficient compared to the bipolar charger. The proposed charger was more advantageous as the target particle size decreased.